2018
DOI: 10.1021/acs.iecr.7b04556
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Microwave Synthesized Mesoporous TS-1 Zeolite for Catalytic Oxidation of Cyclic Olefins

Abstract: A distinctive mesoporous titanium silicalite-1 (TS-1) was prepared by microwave-assisted postsynthetic treatment with H2O2 to generate hierarchical pore structure. For comparison, mesoporous TS-1 was also prepared with alkali or fluoride postsynthetic treatment. Synthesized catalysts were characterized by various techniques, namely, XRD, XPS, FTIR, UV–vis DRS, and others and evaluated for oxidation of cyclic olefins. The post-treated TS-1 with H2O2 and microwave irradiation exhibited a high catalytic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…Experimental conditions: T=80 °C, 1 h reaction time, 50 mmol cyclohexene, 2.5 mmol H 2 O 2 , 200 mg catalyst (3.8 mol.% Ti), 5 ml tert‐butanol (Fraile); [118] T=65 °C, 2 h reaction time, 25 mmol cyclohexene, 5.5 mmol H 2 O 2 , 35 mg catalyst (0.13 mol.% Ti), 5 ml CH 3 CN (Don Tilley) [119] . Additional data for allyl chloride (T=45 °C, 0.5 h reaction time, 45 mmol allyl chloride, 9 mmol H 2 O 2 , 310 mg catalyst [2.1 mol.% Ti], 50 ml methanol) [120] and cyclohexene (T=70 °C, 5 h reaction time, 20 mmol cyclohexene, 20 mmol H 2 O 2 , 100 mg catalyst [1.5 mol.% Ti], 10 ml acetonitrile) [121] conversion over TS‐1 are provided (see details in the text). For these catalysts, the yield is replaced by conversion values of H 2 O 2 and cyclohexene, respectively.…”
Section: Strategies To Improve Ti‐based Heterogeneous Epoxidation Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental conditions: T=80 °C, 1 h reaction time, 50 mmol cyclohexene, 2.5 mmol H 2 O 2 , 200 mg catalyst (3.8 mol.% Ti), 5 ml tert‐butanol (Fraile); [118] T=65 °C, 2 h reaction time, 25 mmol cyclohexene, 5.5 mmol H 2 O 2 , 35 mg catalyst (0.13 mol.% Ti), 5 ml CH 3 CN (Don Tilley) [119] . Additional data for allyl chloride (T=45 °C, 0.5 h reaction time, 45 mmol allyl chloride, 9 mmol H 2 O 2 , 310 mg catalyst [2.1 mol.% Ti], 50 ml methanol) [120] and cyclohexene (T=70 °C, 5 h reaction time, 20 mmol cyclohexene, 20 mmol H 2 O 2 , 100 mg catalyst [1.5 mol.% Ti], 10 ml acetonitrile) [121] conversion over TS‐1 are provided (see details in the text). For these catalysts, the yield is replaced by conversion values of H 2 O 2 and cyclohexene, respectively.…”
Section: Strategies To Improve Ti‐based Heterogeneous Epoxidation Catalystsmentioning
confidence: 99%
“… Microscopy images of a) multilayered MFI titanosilicate, [146] b) Ti‐UTL titanosilicate (in inset is shown a schematic illustration of the zeolite structure), [150] c) conventional TS‐1 (c.1) vs . hierarchical TS‐1 obtained by post‐synthetic treatment with TPAOH (top‐down, c.2), [121] d) conventional TS‐1 (d.1) vs . hierarchical TS‐1 obtained by microwave‐assisted post‐synthetic treatment with H 2 O 2 (top‐down, d.2), [151] e) conventional TS‐1 (e.1) vs .…”
Section: Strategies To Improve Ti‐based Heterogeneous Epoxidation Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, from the analysis of TG‐DTA test, the four catalysts demonstrate different coke resistance, this is possibility associated with the diffusion limitation of catalyst structure . Ogura et al have reported that alkali‐treated H‐ZSM‐5 enhances catalytic performance per Al‐site in the cracking of cumene. This imply that the intra mesopores can increased the rate of mass transfer for bigger molecular.…”
Section: Discussionmentioning
confidence: 99%
“…1 引言 面对环境逐步恶化与资源加速短缺的双重挑战, 能源化工领域开始聚焦于精准催化,力争实现"原料 多元化、过程绿色化、产品高端化"的行业发展目标 [1][2][3][4] 。新的战略目标要求清洁高效地利用化石能源, 加速推动其下游相关高附加值产品的综合利用 [5,6] 。 因此,以炼化一体化带动烯烃下游高端化学品合成, 打造高端化工产业新亮点、 新优势是当前炼化领域的 迫切需求 [7,8] 。其中,烯烃下游的高附加值环氧化学 品作为一种极其重要的有机化工中间体, 被广泛应用 于医药、汽车、食品、农业和建筑等领域 [9][10][11] 。然而 目前除乙烯、丙烯外,部分烯烃环氧化生产采用有机 过氧酸法、氯醇法等环境污染严重或者加工过程复 杂、联产物繁多的工艺流程 [12][13][14][15] ,亟需发展新型绿色 工艺。因此,大力发展绿色环氧化工艺符合绿色化工 可持续发展的战略需求与目标。 以 TS-1 为代表的钛硅分子筛与过氧化氢组成的 环氧化催化体系由于其绿色环保的特性吸引了广泛 的关注 [16][17][18][19][20][21][22] , 该体系已经被广泛应用于一系列反应中 [23][24][25][26] ,例如烯烃环氧化、芳烃的羟基化、环己酮的氨 氧化、烷烃氧化、氧化脱硫以及醇和胺的氧化等(图…”
unclassified